PERAN MEDIASI KNOWLEDGE SHARING PADA PENGARUH QUALITY OF WORK LIFE DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Astitiani, Ni Luh Putu Surya; Sintaasih, Desak Ketut (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 13 Nomor 1 Tahun 2019, 2019)
The purpose of this study is to analyze how the role of knowledge sharing mediation on the influence of quality of work life and job satisfaction on employee performance. This research was conducted at Swastika Bungalows Sanur. The number of samples taken as many as 60 employees with saturated sample method. Data were collected by distributing questionnaires and using Partial Least Square (PLS) analysis as a data analysis technique. The result of this research shows that quality of work life have positive effect on knowledge sharing, job satisfaction has positive effect on knowledge sharing, quality of work life have positive effect on employee performance, job satisfaction has positive effect on performance and knowledge sharing have positive effect on employee performance, the results of this study also revealed that knowledge sharing mediates the influence of quality of work life on employee performance and mediates the effect of job satisfaction on employee performance at Swastika Bungalows Sanur. The practical implication of this research is that it is expected that the study findings can be considered for the management of Swastika Bungalows Sanur in terms of improving the performance of employees with attention to support by taking care of a comfortable working atmosphere, fair compensation, and always increasing employee job satisfaction and knowledge sharing role as mediator for can improve employee performance